Microbial Community Succession and Organic Pollutants Removal During Olive Mill Waste Sludge and Green Waste Co-composting - Bouhia, Youness; Hafidi, Mohamed; Ouhdouch, Yedir; El Boukhari, Mohammed El Mehdi; El Fels, Loubna; Zeroual, Youssef; Lyamlouli, Karim (Frontiers in Microbiology, 2022)
Olive mill wastewater sludge (OMWS) is the main by-product of the olive industry. OMWS is usually dumped in landfills without prior treatment and may cause several eco-environmental hazards due to its high toxicity, which is mainly attributed to polyphenols and lipids. OMWS is rich in valuable biocompounds, which makes it highly desirable for valorisation by composting. However, there is a need to understand how microbial communities evolve during OMWS composting with respect to physicochemical changes and the dynamics of pollutant degradation. In this study, we addressed the relationship between microbial community, physicochemical variations and pollutants degradation during the co-composting of OMWS and green wastes using metagenomic- and culture-dependent approaches. The results showed that in raw OMWS, Pichia was the most represented genus with almost 53% of the total identified fungal population. Moreover, the bacteria that dominated were Zymobacter palmae (20%) and Pseudomonas sp. (19%). The addition of green waste to OMWS improved the actinobacterial diversity of the mixture and enhanced the degradation of lipids (81.3%) and polyphenols (84.54%). Correlation analysis revealed that Actinobacteria and fungi (Candida sp., Galactomyces sp., and Pichia manshurica) were the microorganisms that had the greatest influence on the composting process. Overall, these findings provide for the first time some novel insights into the microbial dynamics during OMWS composting and may contribute to the development of tailored starter inoculum for process optimization